Analisis Strategi Komunikasi Pemasaran Lazatto Unsika 2 Dalam Mempromosikan Produk Kepada Konsumen - Intan Awalia; Fardiah Oktariani Lubis; Made Panji Teguh Santoso (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
\\\\This study aims to analyze the marketing communication strategy used by Lazatto Unsika 2, in promoting its products to consumers. The development process of globalization was initially marked by advances in information and communication technology, which gradually increased rapidly until finally humans were increasingly spoiled by all existing technology. Likewise in the culinary business world, the promotion and transaction process is easier and more practical to do with digital technology. This has led to an increase in consumer interest in culinary products, and has made the culinary industry one of the most profitable industries and has led to more and more entrepreneurs in this field. The results showed that the marketing communication strategy carried out by Lazatto Unsika 2 in promoting products to its customers in Karawang was very well done. The messages and information conveyed by Lazatto Unsika 2 in increasing customer interest in Karawang are carried out with various interesting and unique promos. The promotion process was also quite successful in attracting a lot of customer interest. Keywords: Strategy; Marketing Communication; Promotion